Comparación de los estilos estructurales en la sección entre bogotá y los farallones de medina, cordillera oriental de colombia (1999)
Between the Bogotá area and the Farallones range there is a marked contrast between two structural styles of an opposed vergence. To the east, a distinct marginal high, referred to as Chingaza dome, displays by its asymmetry and its faulted eastern flank an eastern vergence. Open second-order folds, associated to an axial plane cleavage, affect this dome Ptygmatitic folds yield local shortening values of 40"10 along this structural high, but decrease notably toward the adjacent structural depressions. Deformation affects both basement and cover rocks and precludes, by its homogeneous nature, a detachment within the lower Cretaceous shales. On the western extreme of our study region, the anticlines around the Teusaca River display significant amplitudes and steeply inclined to inverted western flanks. Folding occurred by flexural slip and a layer parallel strain is here completely absent. The line-length balancing of these frontal folds yields shortening values of 17%. The geometric properties of these folds require two detachment horizons.  Between these two opposed areas, the Rio Blanco region is affected by an intermediate structural style. Folding of the frontal parts of this fold belt is viewed as a consequence of an uplift and a homogeneous shortening of the Chingaza dome, which prompted a partial detachment of the Cretaceous cover and its gravity-driven displacement toward the structural depression of the Savannah of Bogotá.